The Effect of Family Motivation Interviewing Program on Alcohol Consumption in Schizophrenic Patients with Alcohol Drinking Problem - ปิ่นสุภา, พรินทร; อุทิศ, เพ็ญพักตร์ (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this pretest-posttest with a comparison group research design were to compare: 1) mean scores on alcohol consumption of schizophrenic patients with alcohol drinking problem before and after received The family motivational interviewing program (FMI), and 2) mean scores on alcohol consumption of schizophrenic patients with alcohol drinking problem who received the FMI and those who received regular nursing care. The sample consisted of 40 schizophrenic patients with alcohol drinking problem who met the inclusion criteria and received services at the inpatient department. They were matched-pairs with scores on alcohol drinking problem and then randomly assigned to either experimental or control group, 20 subject in each group. The experimental group received the FMI and the control groups received regular nursing care. Research instruments comprised of: 1) FMI 2) demographic questionnaire, 3) the alcohol consumption assessment 4) the stage of change readiness and treatment eagerness scale 5) Alcohol use disorders identification test and 6) Brief Psychiatric Rating Scale. The 1st and 4th instruments were verified for content validity by 5 professional experts. The reliability of the 3rd instrument was reported by Cronbach’s Alpha coeeficient as of .86. Data were analyzed using descriptive statistics, dependent and independent t-tests.